2020
DOI: 10.1186/s12886-020-01616-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ability of OCT parameters and retinal ganglion cells count in identification of glaucoma in myopic preperimetric eyes

Abstract: Background The aim of the study is to evaluate the diagnostic ability of OCT parameters and retinal ganglion cells (RGCs) count in identify glaucomatous disease in myopic preperimetric eyes. Methods This was a cross-sectional observational study. The study group consisted of 154 eyes: 36 controls, 64 preperimetric (PPG), and 54 primary openangle glaucoma (POAG) eyes. Each group was divided into three subgroups based on axial length: emmetropic, myopic with axial length (AL) < 25 mm, and myopic with AL >… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Seo et al showed that the best RNFL sectors for diagnosing glaucoma in patients with high myopia were the temporal-inferior sector and the inferior quadrant (AUROC were 0.974 and 0.951, respectively) [ 64 ]. Similarly, Rolle et al, using Fourier-Domain-OCT (FD-OCT RTVue-100; Optovue, Fremont, CA, USA), found that the average RNFL yielded the best diagnostic ability for the diagnosis of glaucoma in patients with AXL > 25 mm, followed by the superior and inferior RNFL, reaching AUROC of 0.883, 0.858, and 0.872, respectively [ 73 ]. As the macular parameters are not significantly affected by high myopia, recent studies have established that the macular ganglion cells’ layer thickness has higher diagnostic power and progression analysis than the peripapillary RNFL thickness in high myopia [ 74 , 75 , 76 ], the inferotemporal macular GCIPL thickness being the best parameter for myopic glaucoma discrimination [ 74 ].…”
Section: Rnfl Thickness Measurement By Octmentioning
confidence: 99%
See 1 more Smart Citation
“…Seo et al showed that the best RNFL sectors for diagnosing glaucoma in patients with high myopia were the temporal-inferior sector and the inferior quadrant (AUROC were 0.974 and 0.951, respectively) [ 64 ]. Similarly, Rolle et al, using Fourier-Domain-OCT (FD-OCT RTVue-100; Optovue, Fremont, CA, USA), found that the average RNFL yielded the best diagnostic ability for the diagnosis of glaucoma in patients with AXL > 25 mm, followed by the superior and inferior RNFL, reaching AUROC of 0.883, 0.858, and 0.872, respectively [ 73 ]. As the macular parameters are not significantly affected by high myopia, recent studies have established that the macular ganglion cells’ layer thickness has higher diagnostic power and progression analysis than the peripapillary RNFL thickness in high myopia [ 74 , 75 , 76 ], the inferotemporal macular GCIPL thickness being the best parameter for myopic glaucoma discrimination [ 74 ].…”
Section: Rnfl Thickness Measurement By Octmentioning
confidence: 99%
“…Best diagnostic ability of glaucoma in patients with AXL > 25 mm [ 73 ] Average RNFL: AUROC of 0.883 Superior RNFL: AUROC of 0.858 Inferior RNFL: AUROC 0.872 …”
Section: Figurementioning
confidence: 99%
“…При этом для выявления наиболее чувствительных анатомических критериев глаукомы при близорукости многими авторами проводилась оценка томографических параметров глаукомы при осевой миопии и у близоруких пациентов без глаукомы. Так, было показано, что толщина комплекса ганглиозных клеток с внутренним плексиформным слоем при миопии снижена незначительно, что делает данный показатель особенно ценным для диагностики глаукомы при миопии [9], что и было подтверждено в исследовании диагностической чувствительности для глаукомы таких параметров, как показатель общего объема потерь КГК и толщина комплекса ганглиозных клеток в нижнем секторе макулярной зоны [10,11].…”
Section: Introductionunclassified
“…Glaucoma is the leading cause of visual loss in the world 2. More than 100 million people currently suffer from irreversible visual impairment and blindness due to glaucoma, and the number is estimated to affect 111 million people in 2040, resulting in heavy social health burdens 3,4. However, medical and surgical treatment nowadays could not reverse glaucomatous damage to visual system.…”
mentioning
confidence: 99%
“…suffer from irreversible visual impairment and blindness due to glaucoma, and the number is estimated to affect 111 million people in 2040, resulting in heavy social health burdens. 3,4 However, medical and surgical treatment nowadays could not reverse glaucomatous damage to visual system. Lowing the intraocular pressure (IOP) was the only proved effective way to slow the progression of glaucomatous damages.…”
mentioning
confidence: 99%